RNA Therapeutics - Research and Clinical Advancements - Feng, Rundong; Patil, Suryaji; Zhao, Xin; Miao, Zhiping; Qian, Airong (Frontiers in Molecular Biosciences, 2021)
RNA therapeutics involves the use of coding RNA such as mRNA as well as non-coding RNAs such as small interfering RNAs (siRNA), antisense oligonucleotides (ASO) to target mRNA, aptamers, ribozymes, and clustered regularly interspaced short palindromic repeats-CRISPR-associated (CRISPR/Cas) endonuclease to target proteins and DNA. Due to their diverse targeting ability and research in the RNA modification and delivery systems, it has become possible to develop RNA-based drugs and their investigation in a clinical setting for the treatment of many diseases. Therefore, in this article, we have summarized different RNA therapeutics, their targeting strategies, and clinical progress for various diseases as well as limitations; so that it might help researchers formulate new and advanced RNA therapeutics for various diseases. Additionally, FDA-approved RNA-based therapeutics have also been discussed.